ASEP SUNANDAR SUNARYA: MENJADI DALANG WAYANG GOLEK YANG POPULER - S.Sn., M.Sn., Masyuning (LP2M ISBI Bandung, 2017)
Not many people knew As p Sunandar's journey whom became famous puppeteer in West Java. The topic about As p Sunandar led me to research and write this paper. I began formulating the topic as sinden at As p Sunandar's theater troupe. I know that I was doing ethnomusicology or fieldwork: by getting to know As p Sunandar who make the new style of wayanggol k performances, studying and performing the music itself, and talking to whoever had the patience to listen to me. The conclusion ofpaperwasAs p Sunandarfocused on the innovative nature of the wayang gol k performance.